Ameliorative effects of morel mushroom (Morchella esculenta) against Cadmium-induced reproductive toxicity in adult male rats - Iqbal,T. (2022)
Abstract Cadmium (Cd) is one of the major toxicants, which affects human health through occupational and environmental exposure. In the current study, we evaluated the protective effects of morel mushrooms against Cd-induced reproductive damages in rats. For this purpose, 30 male rats were divided into 6 groups (n=5/group), the first group served as the control group, second group was treated with an intraperitoneal (i.p) injection of 1 mg/kg/day of Cd. Third and fourth groups were co-treated with 1 mg/kg/day of Cd (i.p) and 10 and 20 mg/kg/day of morel mushroom extract (orally) respectively. The final 2 groups received oral gavage of 10 and 20 mg/kg/day of morel mushroom extract alone. After treatment for 17 days, the animals were euthanized, and testes and epididymis were dissected out. One testis and epididymis of each animal were processed for histology, while the other testis and epididymis were used for daily sperm production (DSP) and comet assay. Our results showed that Cd and morel mushrooms have no effect on animal weight, but Cd significantly decreases the DSP count and damages the heritable DNA which is reversed in co-treatment groups. Similarly, the histopathological results of testes and epididymis show that morel mushrooms control the damage to these tissues. Whereas the morel mushroom extract alone could enhance the production of testosterone. These results conclude that morel mushrooms not only control the damage done by Cd, but it could also be used as a protection mechanism for heritable DNA damage.